Evidence for euphotic zone anoxia during the deposition of Aptian source rocks based on aryl isoprenoids in petroleum, Sergipe-Alagoas Basin, northeastern Brazil - Sousa Júnior, Gustavo R.; Santos, AntÔnia L.S.; De Lima, Sidney G.; Lopes, José A.D.; Reis, Francisco A.M.; Santos Neto, Eugênio V.; Chang, Hung K. [UNESP] (Elsevier, 2013)
Four crude oil samples from the Sergipe-Alagoas Basin, northeastern Brazil, were analyzed using full scan gas chromatography-quadrupole mass spectrometry (GC-qMS) for biomarkers, in order to correlate them using aromatic carotenoids thereby enhancing knowledge about the depositional environment of their source rocks. The geochemical parameters derived from saturated fractions of the oils show evidence of little or no biodegradation and similar thermal maturation (Ts/(Ts+Tm) for terpanes, C29 αββ/(αββ+ααα), C27, and C29 20S/(20S+20R) for steranes). Low pristane/phytane ratios and the abundance of gammacerane and β-carotane are indicative of an anoxic and saline depositional environment for the source rocks. Moreover, we identified a large range of diagenetic and catagenetic products of the aromatic carotenoid isorenieratene, including C40, C33, and C32 diaryl isoprenoids and aryl isoprenoid derivatives with short side chains and/or additional rings. These results indicate anoxia in the photic zone during the deposition of the source rocks. © 2013 The Authors.
Keywords: Depositional environment; Euphotic zone; Gas chromatography-quadrupole mass spectrometry; Geochemical parameters; Northeastern Brazil; Short side chains; Source rocks; Thermal maturation; Aromatic compounds; Biodegradation; Biomarkers; Gas chromatography; Lipids; Mass spectrometry; Petroleum industry; Pigments; Rocks; Deposition; anoxic conditions; Aptian; biodegradation; biomarker; carotenoid; crude oil; euphotic zone; gas chromatography; isoprenoid; mass spectrometry; source rock; Atlantic Ocean; Brazil; Sergipe-Alagoas Basin